If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -22 = Y Reorder the terms: -22 + X = Y Solving -22 + X = Y Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + X = 22 + Y Combine like terms: -22 + 22 = 0 0 + X = 22 + Y X = 22 + Y Simplifying X = 22 + Y
| 22-5x=7x+10 | | (x^2+1)*2.25=x^2+1+2.25 | | 6y-4y=-8+2 | | 6b-5a=4 | | f(x)=-3x^2+2x+4 | | 7p+2q=-5 | | 4xln(x)=0 | | 2t+11=34 | | 4s=29 | | x^3-2.25x^2=-3.25 | | 252-9n=170 | | 20-120/7 | | -33=3x+-6 | | 2y+4x=11yequal | | 252-9n=168 | | 13x-5=4x-9 | | n*1.5*6=28-n*0.5*6 | | 3n+9n=28 | | ax-3x=4 | | N=28-3 | | -v+5+6v=1+5v+3 | | 3p+6=11p-1 | | 7777=8 | | 1+4y=17 | | 2(x-7)=6(-9) | | 6q-26=50-1/3q | | 32x^3+36x^2-4=0 | | 933=(10x-150)*ln(2x-29) | | 2x/12x^2 | | 9(x-7)=2(5x+7) | | -2sin[3(x-180/4)] | | x^2+2y^2=99 |